Influência de fatores ambientais na distribuição espacial de uma comunidade de anuros em área de altitude no domínio das caatingas - Xavier, Ariane Lima (2013)
The present study searched for associations between an anuran community composition and environment variables to test which variable would better explain spatial patterns of anurans within a mountain environment covered by semidecidual forests and rocky mountain fields. The study area was a State Park in the Municipality of Miguel Calmon, Bahia State, Brazil, an area comprised in the Caatinga Morphoclimatic Domain. We sampled 20 plots by active method during two rainy seasons, and measured 13 environment variables. The environment matrix was reduced to four synthetic axes by the principal component analysis (PCA), and anuran community (abundance matrix) was reduced to a single synthetic axis by the nonmetric multidimensional scaling method (NMS). We tested the absence of association between environment axes (PCA) and community composition (NMS axis) by multiple regression analysis. The PC1 (40%) was the only axis significantly associated to anuran composition, in which variables with major contributions were directly related to the vegetation structure. The anuran community was ordered along an environment gradient, from open areas featured by rocky mountain fields (“Campo Rupestre”) to primary semidecidual mountain forest patches. Anuran composition in Sete Passagens State Park is very distinct from those in Caatinga, which denotes the importance in considering both phytophysiognomies to create protection areas in the Brazilian semi-arid.